Repositioning agricultural support policies for achieving China’s 2060 carbon neutrality goal - Feng, Xialong; Zhang, Yumei; Wu, Zongyi; Fan, Shenggen; Chen, Kevin Z. (2022)
Agrifood systems are both a contributor to greenhouse gas (GHG) emissions and an important sector for achieving China’s 2060 carbon neutrality goal and mitigating climate change. Rising global temperatures and frequent extreme weather have greatly weakened agricultural production capacity (IPCC, 2021). The need to mitigate climate change by reducing GHG emissions has global consensus. In 2020, the Chinese government made an important commitment toward peaking its carbon dioxide emissions by 2030 and achieving carbon neutrality by 2060. Under China’s 2060 carbon neutrality goal, the contribution of agrifood systems to GHG emissions reduction cannot be ignored. According to estimates by the Academy of Global Food Economics and Policy (AGFEP) at China Agricultural University (AGFEP, 2021), GHG emissions from agrifood systems reached 1.09 billion metric tons (t) of CO2eq in 2018, accounting for 8.2 percent of total national GHG emissions. While ensuring food security as the top national priority, the combined measures can reduce GHG emissions by 47 percent by 2060, compared to 2020 levels; these measures include improving agricultural technologies, reducing food loss and waste, and shifting dietary patterns. When coupled with the carbon sequestration of land use, land-use change and forestry (LULUCF), agrifood systems can contribute significantly to achieving carbon neutrality (AGFEP, 2021).